PENGARUH KEPRIBADIAN DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA KANTOR KEMENTERIAN AGAMA KOTA PEMATANGSIANTAR - Fatmala, Kiki; Lie, Darwin; Efendi, Efendi; Nainggolan, Lora Ekana (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2019)
The suggestation of this research results are: 1. To improve personality employees in carrying out tasks should pay attention to the time and result of what is done. 2. To increase motivation it is better if agencies provide bonuses or incentives and hold annual or monthly holidays so that they can increase the motivation and work spirit of employee. 3. To improve the employee performance of employees should complete their tasks according to the targets set by the agency.Â Keywords: Personality, Motivation, and Employee Performance